Seismic Tomography of Eastern Tibet: Implications for the Tibetan Plateau Growth. Issue 9 (4th September 2018) - Zhang, Fengxue; Wu, Qingju; Li, Yonghua; Zhang, Ruiqing; Sun, Lian; Pan, Jiatie; Ding, Zhifeng
Abstract: The eastern region of the Tibetan Plateau and surrounding regions have gentle to moderate topographic gradients, contrasting the steep margins in northern and southern Tibet. The mechanisms for plateau growth in eastern Tibet are uncertain so far. Here we present a new shear wave tomography model of the Tibetan Plateau derived from S wave traveltimes from teleseismic waveforms recorded by the dense ChinArray seismic network. The model reveals the deep structures beneath the eastern region of the Tibetan Plateau and its adjacent regions, showing clear velocity contrast boundaries roughly along the eastern margins of the Tibetan Plateau. We interpret the slow velocity anomalies beneath the Tibetan Plateau as soft lithosphere, which absorbed most of the northeastward push of the Indian Plate, while the fast velocity anomalies beneath the region surrounding the plateau represent craton‐like rigid block roots. The deformation of the soft/weak lithospheric mantle beneath the Tibetan Plateau is constrained by the convergence between the Indian and Eurasian plates, and the framework of the surrounding rigid blocks. We suggest that weak lithosphere deformation (horizontal shortening and vertical stretching) accounts for the plateau growth in eastern Tibet. Key Points: A 3‐D tomographic S model is proposed using a large‐scale dense seismic array The model shows clear velocity contrast boundaries roughly along the eastern margins of the Tibetan Plateau Plateau growth in eastern Tibet is due to the deformation of weak lithosphere squeezed by surrounding rigid blocks